Reluctance Versus Urge to Disclose Child Maltreatment: The Impact of Multi-Type Maltreatment. Issue 18 (September 2019) - Lev-Wiesel, Rachel; First, Maya; Gottfried, Ruth; Eisikovits, Zvi
Child maltreatment is a major public health issue in Israel. According to a recent Israeli national epidemiological survey, approximately half of Jewish and Arab girls and boys between the ages 12 and 17 experienced at least one type of child maltreatment, at any severity level. The purpose of the present study was to investigate the influence of multi-type maltreatment on Israeli children and youth survivors' reluctance versus urge to disclose; with the effects of gender, age, and ethnicity taken into account. The study is important since non-disclosure has deleterious effects in terms of continuation of the abuse, delays in criminal prosecution and commencement of treatment. A self-report questionnaire incorporating the following instruments was administered: the Juvenile Victimization Questionnaire, the Childhood Trauma Questionnaire, and the Disclosure of Trauma Questionnaire. The sample consisted of 6, 253 Jewish and Arab children and youth who reported experiencing at least one lifetime child maltreatment event. Study results indicated that children and youth's reluctance to disclose is positively associated with their emotional reactions to disclosure, as well as with higher instances of child maltreatment exposure; whereas urge to talk is negatively correlated with their emotional reactions to disclosure.